Teaching readiness and capability of island school teachers in the district of Concepcion Iloilo - Lorelie Sylvie Sente; Ivy Gorriceta (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Teaching readiness and capability of teachers’ mirror the quality of students’ achievements. The determination of readiness and capability of teachers particularly in island schools identified the extent of teachers’ competence despite online skill inadequacies amidst the pandemic. The study included a relationship of personal factors that have bearing on teachers’ readiness and capability. Descriptive-correlational research design was used with simple random sampling. One hundred seventy-two (172) teachers provided the needed data. Data were gathered through a researcher-made questionnaire. The statistical tools used were descriptive statistics, t-test and One-Way ANOVA for significant difference and Pearson r for relationship of teaching readiness and level of teachers’ capability. The findings highlighted teachers’ teaching readiness as high particularly in the preparation of instructional materials and average as to technological requirements such as in place internet access, with computers, laptops, other digital gadgets and delivery of students’ academic needs using technology. While the teachers were highly capable in online skills like creating models, guides, online assessment materials and use of articles, videos and infographics. In the new normal class management, teachers demonstrated very high capability in stimulating student’s curiosity in learning by integrating real life situations, detailed modules and providing an engaging environment through oral communication. No significant differences were found on the degree of teaching readiness and level of teachers’ capability when respondents were grouped according to their selected profile. However, teaching readiness has significant bearing on teachers’ online capability.